Newtop: a fault-tolerant group communication protocol - Ezhilchelvan, P.D.; Macedo, R.A.; Shrivastava, S.K. (Proceedings of 15th International Conference on Distributed Computing Systems, 1995)
A general purpose group communication protocol suite called Newtop is described. It is assumed that processes can simultaneously belong to many groups, group size could be large, and processes could be communicating over the Internet. Asynchronous communication environment is therefore assumed where message transmission times cannot be accurately estimated, and the underlying network may well get partitioned, preventing functioning processes from communicating with each other. Newtop can provide causality preserving total order delivery to members of a group, ensuring that total order delivery is preserved for multi-group processes. Both symmetric and asymmetric order protocols are supported, permitting a process to use say symmetric version in one group and asymmetric version in other.